Study of Nickel Extraction Process from Spent Catalysts with Hydrochloric Acid Solution: Effect of Temperature and Kinetics Study - Ivanna Crecentia Narulita Simanungkalit; Elsha Pamida Bahri; Ratna Frida Susanti; Gelar Panji Gemilar; Widi Astuti; Himawan Tri Bayu Murti Petrus; Kevin Cleary Wanta (Universitas Sanata Dharma, 2021)
As one of the hazardous and toxic solid wastes, spent catalysts need to be treated before the waste is discharged into the environment. One of the substances that need to be removed from the spent catalysts is the heavy metal ions and/or compounds contained therein. The method that can be applied is the extraction method using an acid solvent. In this study, the extraction process was carried out on spent catalysts samples from PT. Petrokimia Gresik. The focus of the study is on nickel extraction by varying the temperature in the range of 30–85 oC. A 1 M hydrochloric acid (HCl) solution was used as a solvent while the extraction process was 120 minutes. The experimental results show that the maximum nickel recovery of 14.70% can be achieved at a temperature of 85 oC. Kinetic studies were carried out using two kinetic models. The results of both models evaluation on the research data show that the lump model gives better results than the shrinking core model. The average error percentage of the lump model is smaller than the shrinking core model. It indicates that the extraction process was controlled by the diffusion step through the ash layer in the solid and chemical reactions simultaneously.